Commitment Model for Construction Workforce in East Kalimantan - Yanti, Yanti; Simanjuntak, Manlian Ronald A.; Jin, Oei Fuk (International Journal of Innovative Research and Scientific Studies, 2025)
This research highlights the strong project performance in East Kalimantan despite challenges such as geographical distance from skilled construction labor, limited material resources, and complex supply chains. The research focuses on the commitment of professional construction workers as a stabilizing factor influencing project outcomes. It aims to examine the effects of Authentic Leadership, Work-Life Balance, and Motivation on employee commitment and project performance. Using an Explanatory Sequential Mixed Method approach, the study involves 250 respondents from contractor companies, analyzed through SEM SmartPLS, and includes qualitative insights from company leadership. Findings reveal that Authentic Leadership and Motivation significantly impact both employee commitment and project performance. Conversely, Work-Life Balance shows a significant negative influence on both variables. Additionally, employee commitment significantly enhances project performance. The study develops a commitment model for professional construction workers to sustain project performance in East Kalimantan and provides practical recommendations for contractor companies’ implementation.